Construction Of Human Lymphatic Filariasis Antibody Phage Display Library And Production Of Recombinant Monoclonal Antibodies Against BmR1 And BmSXP Filarial Antigens - Rahumatullah, Anizah (2018)
A Global Programme for Elimination of Lymphatic Filariasis aims to eliminate the disease as a public health problem by the year 2020. Brugia Rapid and PanLF Rapid are rapid diagnostic tools that are being used in this programme. They are based on the detection of recombinant proteins BmR1 and BmSXP. The quality of these tests should be well-maintained at all time or even improved as the GPELF progresses and a sensitive and specific test may be needed at the end of the programme and for surveillance post-certification. To address this need, the availability of recombinant monoclonal antibodies to the two recombinant proteins would be very useful.